THE USE OF ARTIFICIAL INTELLIGENCE IN THE DIAGNOSIS OF CHILDHOOD AUTISM (BioLaw Journal - Rivista di BioDiritto, 2024)
Starting from the experience of a research group at Stanford University, who is experimenting an AI medical device to analyse the voice and identify typical alterations, thus arriving at a possible diagnosis of autism spectrum disorder, the present research proposed a brief overview of the risks, benefits and of the regulatory corpus applicable today in the European territory and some considerations regarding bias and diagnostic error and the protection tools to guarantee ethical and reliable AI, also in light of the debate on product liability with artificial intelligence.
Keywords: autism; access to care; medical devide; bias; diagnostic error